2009
DOI: 10.1096/fj.08-121459
|View full text |Cite
|
Sign up to set email alerts
|

Altered Ca 2+ dependence of synaptosomal plasma membrane Ca 2+ ‐ATPase in human brain affected by Alzheimer's disease

Abstract: High-affinity Ca(2+) transport ATPases play a crucial role in controlling cytosolic Ca(2+). The amyloid beta-peptide (Abeta) is a neurotoxic agent found in affected neurons in Alzheimer's disease (AD) that has been implicated in dysregulation of Ca(2+) homeostasis. Using kinetic assays, we have shown that the Ca(2+) dependencies of intracellular Ca(2+)-ATPase (SERCA and SPCA) activity are the same in human AD and normal brain but that of plasma membrane Ca(2+)-ATPase (PMCA) is different. The addition of Abeta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
67
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 41 publications
9
67
0
Order By: Relevance
“…PMCA activity in human brain tissue from Alzheimer's disease patients shows an altered dependence on Ca 2+ compared to control brain with stimulation of activity at lower concentrations and less inhibition at high Ca 2+ concentrations [100] suggesting that the affinity of the stimulatory site for Ca 2+ increases and that for the inhibitory site decreases in Alzheimer's brain. More interestingly, addition of amyloid beta peptide to control brain altered its Ca 2+ dependency to resemble that of Alzheimer' s disease brain [100] . In preliminary studies on human brain tissue from Parkinson's disease, we have observed a significant reduction in PMCA activity compared to agematched controls [101] .…”
Section: The Pmcas and Neurodegenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…PMCA activity in human brain tissue from Alzheimer's disease patients shows an altered dependence on Ca 2+ compared to control brain with stimulation of activity at lower concentrations and less inhibition at high Ca 2+ concentrations [100] suggesting that the affinity of the stimulatory site for Ca 2+ increases and that for the inhibitory site decreases in Alzheimer's brain. More interestingly, addition of amyloid beta peptide to control brain altered its Ca 2+ dependency to resemble that of Alzheimer' s disease brain [100] . In preliminary studies on human brain tissue from Parkinson's disease, we have observed a significant reduction in PMCA activity compared to agematched controls [101] .…”
Section: The Pmcas and Neurodegenerationmentioning
confidence: 99%
“…The relationship between the PMCAs and Alzheimer's disease, the most common age-dependent neurodegenerative disorder, was first suggested by a reduction in PMCA activity in neurons exposed to the amyloid beta peptide [97][98][99] . Recent studies have further established the involvement of the PMCA in Alzheimer's disease [100] . PMCA activity in human brain tissue from Alzheimer's disease patients shows an altered dependence on Ca 2+ compared to control brain with stimulation of activity at lower concentrations and less inhibition at high Ca 2+ concentrations [100] suggesting that the affinity of the stimulatory site for Ca 2+ increases and that for the inhibitory site decreases in Alzheimer's brain.…”
Section: The Pmcas and Neurodegenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased ATPase activities have been associated with a number of pathological states including autism, Alzheimer's disease, Parkinson syndrome, Cushing's syndrome (Berrocal et al, 2009;Ji et al, 2000;Wambach et al, 1980). Brain-region specific increases in the activities of Na + /K + ATPase and Ca 2+ Mg 2+ ATPase have also been reported in neurodisorders such as autism and Alzheimer disease.…”
Section: +mentioning
confidence: 99%
“…Complex alternative splicing processes at a site in the first cytosolic loop of the pump, and within the C-terminal calmodulin-binding domain, generate numerous pump variants with special properties. Our group has been studying PMCAs, with a special interest in PMCA4 because this isoform is quite abundant in brain [10] and functional inhibition, loss, mutation or inefficient expression of specific PMCA4 isoforms are associated to different pathologies including several neuropathies [10,11]. In fact, this isoform seems to be functionally inhibited by molecular markers of Alzheimer disease (AD), such as amyloid b-peptide (Ab) and tau [10,12].…”
Section: Introductionmentioning
confidence: 99%